Construction and Characterization of a Human Chromosome 2-Specific BAC Library - Wang, M.; Chen, X.-N.; Shouse, S.; Manson, J.; Wu, Q.; Li, R.; Wrestler, J.; Wrestler, J.; Sun, Z.-G.; Korenberg, J.; Lai, E.
We have constructed a human chromosome 2-specific bacterial artificial chromosome (BAC)library using DNA from the somatic cell hybrid GM10826. The average size of the clones is about 63 kb. The coverage and distribution of the library were estimated by screening with known polymorphic genetic markers and fluorescence in situ hybridization (FISH). Twentyone markers tested positive when DNA pools prepared from approximately one-sixth of the library were screened with 33 known markers. This is consistent with the theoretical calculation of 63